A Case Study on Tropical Bed Bug, Cimex hemipterus (Hemiptera: Cimicidae) Infestation and Management in Dormitories - Kong, Delong; Han, Dongliang; Zhai, Ruyue; Wang, Changlu; Zhang, Jingsheng; Xia, Yanwei; Nian, Xiaoge; Liu, Chaofeng; He, Yurong; Wang, Desen (Journal of economic entomology, 2023)
Numerous bed bug research papers have been published in the past 20 yr as a result of bed bug (Cimex spp.) (Hemiptera: Cimicidae) resurgence in the world.Yet, few of them focused on the management of the tropical bed bug, C. hemipterus (F.). Here, we describe a case of tropical bed bug infestation in two dormitory buildings and effectiveness of a tropical bed bug treatment program. The study site consisted of 125 dormitories in two buildings. An initial building-wide monitoring with ClimbUp interceptors revealed 25 infestations. The spatial distribution of bed bug infested rooms showed a significant aggregated distribution pattern with same infestation status for neighboring units sharing walls. All infested rooms were monitored every 2 wk and treated using a combination of steam and diatomaceous earth (DE) dust application if bed bugs were still found. For the 25 initially identified infested rooms, after 14 wk treatment, 44% of them no longer had bed bugs, and the mean number of bed bugs captured per room decreased by 94.1%. A combination of steam and DE dust treatment is an effective strategy for suppressing tropical bed bug infestations in dormitory environment.